Glaucoma in Costa Rica. Initial approaches - Chavarría-Soley, Gabriela (2004)
Glaucoma is the second most frequent cause of irreversible blindness worldwide. Genetic factors havebeen implicated in the development of the disease. So far six loci (GLC1A-GLC1F) and two genes(TIGR/MYOC and OPTN) are involved in the development of juvenile (JOAG) and adult onset or chronic primaryopen angle glaucoma (COAG), while two loci (GLC3A,GLC3B) and one gene (CYP1B1) are known forprimary congenital glaucoma (PCG). Here we summarize the results of the first genetic studies of glaucoma inCosta Rica. Nine families: 1 with JOAG, 1 with PCG and 7 with COAG were screened for mutations at theknown genes. A10 bp duplication, 1546-1555dupTCATGCCACC, at the CYP1B1 gene, causes, in homozygousstate, glaucoma in the consanguineous PCG family. This mutation has been found in different countries and generatesan early stop codon that termitates protein synthesis 140 amino acids earlier than the normal allele. Inexon 1 of the TIGR/MYOC the innocuous Arg76Lys variant was found in two of the COAG families. In theOPTN gene two variants in the coding region (Thr34Thr, Met 98Lys) and 7 intronic changes were found in otherCosta Rican glaucoma patients. One of the COAG families was chosen for a genome scan with 379 microsatellitemarkers and linkage analysis. LOD scores “suggestive” of linkage were obtained for several chromosomalregions. Evidence indicates that hereditary glaucoma in Costa Rica is highly heterogeneous and that furtherstudies in the country will probably disclose some up to now unknown genes responsible for the disease